The ways racism emerged in the era of President Donald Trump and its impact on Asian-Americans during COVID-19: A sentiment analysis - Ani Windarti; Clarissa Bella Ambar Kusuma; Zanuwar Hakim Atmantika; Kasiyarno Kasiyarno; Didik Murwantono (EduLite: Journal of English Education, Literature and Culture, 2023)
An increase in racist acts of violence against people of Asian descent, ranging from verbal abuse to physical violence, with victims of young children to the elderly in various states. Although not the first in US history, the various cases of post-Donald Trump racist attacks are very worrying for their development, because they occur so frequently and threaten the lives of those who are targeted, particularly Americans of Chinese descent. This widespread racist attack that occurred in almost all US states is unprecedented in the country's long history, following racist acts that have been directed against black people. This article aims to find out how racism became commonplace in the United States under President Trump. Are there factors behind the increase in racism in the United States, especially during a pandemic? To identify the problem, the authors conducted a literature study and observations on social media. The authors used a qualitative approach with sentiment analysis in this study. The result of this study is that Donald Trump's leadership during the pandemic had a massive impact on America and the world, namely racial discrimination against Asia-America.